Scientometric investigation of global carbon nanotubes research. (1st January 2014) - Sagar, Anil; Kademani, B.S.; Girap, Priya V.; Bhanumurthy, K.
On the basis of Web of Science database, through scientometrics, quantitative and qualitative research was conducted on carbon nanotubes literature produced globally. A total of 64, 376 publications and 1, 770, 339 citations were received to these publications during 1992–2012. It was found that the number of published articles was higher in Peoples Republic of China, USA, Japan, South Korea, Germany, France, England, India, etc. The highest number of publications 10, 375 (16.12%) was published in 2012. The highest number of citations 165, 515 (9.35%) was received in 2005. The highest average citations per publication 498.25 was in 1992. The highest growth rate (387.50%) was observed in 1993. Overall Collaboration Coefficient (CR) was very high.